Enhanced Efficacy of Peroxyacetic Acid Against Listeria monocytogenes on Fresh Apples at Elevated Temperature - Shen, Xiaoye; Sheng, Lina; Gao, Hui; Hanrahan, Ines; Suslow, Trevor V.; Zhu, Mei-Jun (Frontiers in Microbiology, 2019)
Peroxyacetic acid (PAA) is widely applied in fresh apple packing facilities to reduce foodborne pathogens on fresh apples. However, there is limited data regarding its practical efficacy against Listeria monocytogenes on fresh apples. This study evaluated the antimicrobial activity of PAA against L. monocytogenes on fresh apples applicable to current industry practice, and further examined practical parameters impacting its efficacy in order to maximize the biocidal effects. Apples were inoculated with a three-strain mixture L. monocytogenes at ~ 6.0 Log10 CFU/apple then subjected to comparative antimicrobial treatments after 48 h post-inoculation. An 80 ppm PAA treatment, at 30-s and 2-min exposure, reduced L. monocytogenes on Granny Smith apples (GSA) by ~1.3 or 1.7 Log10 CFU/apple, respectively. Water hardness or pH condition of the PAA solution did not affect efficacy of PAA. However, increasing PAA wash water temperature from 22 to 43 °C or above markedly enhanced the biocidal activity of PAA against L. monocytogenes on the GSA surface. A 2-min contact time of 80 ppm PAA at 43 and 46 °C resulted in a 2.3 and 2.6 Log10 CFU/apple reduction, respectively. A 30-s contact time of 80 ppm PAA at 43-46 °C reduced L. monocytogenes on GSA by 2.2-2.4 Log10 CFU/apple. Similarly, PAA intervention at elevated temperatures significantly strengthened its effectiveness against naturally-occurring apple microbiota. A 2-min exposure of 80 ppm PAA reduced total plate count (TPC) and yeasts/molds count (Y/M) by 1.54 and 2.13 Log10 CFU/apple, respectively. PAA treatment 43-46 C can provide a vital method to improve antimicrobial efficacy against both L. monocytogenes and indigenous microbiota on fresh apples. Our data provide valuable information and reference points for the apple industry to further validate or verify process controls in compliance with industry expectations and with federal preventive control requirements. It also provides baseline parameters for an alternative intervention method for the apple industry to improve antimicrobial efficacy against foodborne pathogens.